PENGARUH EDUKASI GIZI DENGAN MEDIA PUZZLE TERHADAP PENGETAHUAN DAN SIKAP TENTANG SAYUR DAN BUAH PADA ANAK SEKOLAH DASAR - Safitri, Yeni Liza; Sulistyowati, Enik; Ambarwati, Ria (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2021)
Background: Consumption of vegetables and fruit among school age children is still low due to lack of knowledge and attitudes about vegetables and fruit. Nutrition education can be provided to increase knowledge and attitudes as early as possible. Nutrition education using puzzle media is expected to increase knowledge and form a positive attitude about vegetable and fruit consumption.Objective: To determine the effect of nutrition education using puzzle media towards knowledge and attitudes about vegetables and fruit in elementary school children.Methods: This was a quasi-experimental study with pretest-posttest control group design. Fourty elementary school children were divided into two groups. The treatment group received nutrition education using puzzle media and a control group received nutrition education without puzzle media. Knowledge and attitudes were assessed before and after the study based on scores. Data were analyzed using Paired T-Test and Independent Sample T-Test.Results: The average score od knowledge in the treatment group increase by 18.25 points and the control group scre increased by 12.25 points. The mean score of attitudes in the treatment group increased by 14.45 points and the control group (p=0.014) and the attitude scores between the treatment group and the control group (p=0.003)Conclusion: Nutrition education using puzzle media can increase knowledge and attitudes about vegetables and fruit in elementary school children.Keywords: Nutrition education; Puzzle media; Vegetable and fruit; Knowledge; Attitude.